Delayed full-state feedback control of airfoil flutter using sliding mode control method. (February 2016) - Luo, Mengxiang; Gao, Mingzhou; Cai, Guoping
Abstract: This paper studies the delayed feedback control of flutter of a two-dimensional airfoil using a sliding mode control (SMC) method. The dynamic equation of airfoil flutter is firstly established using the Lagrange method, in which the cubic hardening spring nonlinearity of pitch stiffness is considered. Then, the state equation with time delay is transformed into a standard state equation with implicit time delay by a special integral transformation. Next a nonlinear time-delay controller is designed using the SMC method. Finally the effectiveness of the proposed controller is verified through numerical simulations. Simulation results indicate that time delay in the control system has significant influence on the control performance. Control failure may happen if time delay is not considered in control design. The time-delay controller proposed is effective in suppressing the airfoil flutter with either small or large control time delay. Highlights: The dynamic equation considering cubic hardening spring nonlinearity is established. A treating method for time delay in the active control system is proposed. The proposed time-delay controller is available for both small and large time delay.